Multi-omics analysis of copper metabolism-related molecular subtypes and risk stratification for osteosarcoma - Yang Zhang; Wen Liu; Dayong Liu; Xiaopeng Li; Qingshan Zhuang; Quan Sun; Xiaolin Wu; Feng Li (Discover Oncology)
Abstract Background As the most common primary malignant bone tumor, further investigation into risk stratification for osteosarcoma (OS) prognosis is of significant clinical importance. Copper is essential for bone metabolism; however, its specific role in OS remains unclear. Methods The expression characteristics of copper metabolism related genes (CORGs) in OS were revealed by single cell sequencing. Prognosis-associated CORGs were identified, and a CORG-related scoring system and risk model were established using bioinformatics approaches, including univariate and multivariate Cox regression analyses and LASSO analysis. We further analyzed immune microenvironment infiltration, molecular subtypes and clinicopathological characteristics. The impact of selected CORG with high-risk coefficient on OS cells was tested by qRT-PCR, western blot, siRNA, colony formation analysis and Transwell in vitro. Results We successfully developed an OS scoring system related to copper metabolism and validated its independent prognostic value in patients with OS. The potential clinical value of CORG scoring system was analyzed. APOA4 was selected for in vitro experiments and its effect on the proliferation and invasion ability of OS cells was verified. Conclusion We established a copper metabolism-related scoring system to effectively stratify the risk of OS patients. Our results provide a new basis for the role of copper metabolism in OS and provide new potential targets for the treatment of OS.